2019
DOI: 10.5194/acp-19-2149-2019
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of atmospheric CO2 at KMA GAW regional stations, its characteristics, and comparisons with other East Asian sites

Abstract: To understand the carbon cycle at policy-relevant spatial scales, a high density of high-quality CO 2 measurement sites is needed. In 2012, the Korea Meteorological Administration (KMA) installed CO 2 monitoring systems at Anmyeondo (AMY) in the west, Jejudo Gosan Suwolbong (JGS) in the southwest, and Ulleungdo (ULD) in the east of South Korea. Three stations were instrumented with identical greenhouse gas measurement systems based on cavity ring-down spectroscopy (CRDS) and a new drying system developed by KM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 34 publications
4
33
0
Order By: Relevance
“…Although the CM mission was unable to cover the whole day of each month, that the observed values compare well with the observations at AMY and Gosan (33.30 ˚N, 126.16 ˚E) GAW background stations in Korea, which show a minimum in August and a maximum in April [14]. As per a previous study, the CO2 observed in the vicinity of megacity regions (Nanjing, Beijing, Shanghai, and Lin'an) showed high levels in winter, but in spring in remote stations (AMY, Gosan, Waliguan, and Shangdianzi) in Northeast Asia [14,34]. This is likely due to stronger biogenic emissions in spring with rising air temperature in rural and remote sites compared to densely-populated urban sites with higher fossil fuel emissions in winter.…”
Section: Spatio-temporal Co 2 and Ch 4 Variations Over Western Koreasupporting
confidence: 79%
See 3 more Smart Citations
“…Although the CM mission was unable to cover the whole day of each month, that the observed values compare well with the observations at AMY and Gosan (33.30 ˚N, 126.16 ˚E) GAW background stations in Korea, which show a minimum in August and a maximum in April [14]. As per a previous study, the CO2 observed in the vicinity of megacity regions (Nanjing, Beijing, Shanghai, and Lin'an) showed high levels in winter, but in spring in remote stations (AMY, Gosan, Waliguan, and Shangdianzi) in Northeast Asia [14,34]. This is likely due to stronger biogenic emissions in spring with rising air temperature in rural and remote sites compared to densely-populated urban sites with higher fossil fuel emissions in winter.…”
Section: Spatio-temporal Co 2 and Ch 4 Variations Over Western Koreasupporting
confidence: 79%
“…Such trans-boundary pollutant transports go through the lower troposphere, including the atmospheric boundary layer and lower free atmosphere in the Korean region, and have been frequently observed in airborne and surface measurements [14][15][16]. Previous studies also show that Korean domestic emissions play an important role in determining the air quality in Korea [14] based on the Korea-United States Air Quality (KORUS-AQ) field campaign, which was performed based on an international collaboration between the Republic of Korea (hereafter Korea) and the United States, led by the National Institute of Environmental Research of Korea and the National Aeronautics and Space Administration (NASA), respectively. The KORUS-AQ campaign was conducted over Korea and its surrounding regions for the period from May to June 2016, and observations obtained from the campaign were utilized to quantify the contribution towards understanding air quality and factors controlling air quality in the region.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…The analysis methods for ( 14 CO 2 ) are described by Lehman et al (2013). Measurement repeatability of ( 14 CO 2 ) in aliquots of whole air extracted from surveillance cylinders is 1.8 ‰ (1σ ), roughly equating to 1 µmol mol −1 C ff detection capability from the measurement uncertainty alone.…”
Section: Sampling Site and Methodsmentioning
confidence: 99%